Speech Rhythm Variation in Early-Stage Parkinson's Disease: A Study on Different Speaking Tasks - Maffia, Marta; De Micco, Rosa; Pettorino, Massimo; Siciliano, Mattia; Tessitore, Alessandro; De Meo, Anna (Frontiers in Psychology, 2021)
Patients with Parkinson’s Disease (PD) usually reveal speech disorders and, among other symptoms, the alteration of speech rhythm. The purpose of this study is twofold: a) to test the validity of two acoustic parameters - %V, vowel percentage, and VtoV, the mean interval between two consecutive vowel onset points - for the identification of rhythm variation in early-stage PD speech; and b) to analyze the effect of PD on speech rhythm in two different speaking tasks, reading passage and monologue. A group of 20 early PD patients was involved in the study and compared to 20 age and sex-matched healthy controls. The results of the acoustic analysis confirmed that %V is a useful cue for early PD speech characterization, having significantly higher values in patients’ productions than in healthy control (HC) speech. A simple speaking task, such as the reading task, was found to be more effective than spontaneous speech in rhythmical variations’ detection.